Mexico and the Internet Treaties, 1996–2010: International Pressure, Domestic Politics - Haggart, Blayne (Copyfight, 2014)
To get a sense of the extent to which copyright has been politicized since the Internet treaties were signed in December 1996, we should consider the events, oceans apart, of 11 February 2012 and 20 July 2011. The former date witnessed a scene that would have been unthinkable a decade earlier: massive European protests against anintellectual property treaty. Throughout Europe, tens of thousands of people – organizers put the number at more than 100,000¹ – took to the streets to protest the Anti-Counterfeiting Trade Agreement (ACTA), the US-led treaty discussed in chapter 6.The Guardiannewspaper put the number